2017
DOI: 10.1021/acs.jpca.7b08004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Nucleation and Crystal Growth and Mass Transfer in Internally Mixed Sucrose/NaNO3 Particles

Abstract: Secondary organic aerosols (SOA) can exist in a glassy or semisolid state under low relative humidity (RH) conditions, in which the particles show nonequilibrium kinetic characteristics with changing ambient RH. Here, we selected internally mixed sucrose/NaNO droplets with organic to inorganic molar ratios (OIRs) of 1:8, 1:4, 1:2, and 1:1 as a proxy for multicomponent ambient aerosols to study crystal nucleation and growth processes and water transport under a highly viscous state with the combination of an RH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Despite the abundant mass of inorganic species in the atmosphere (Jimenez et al, 2009;Cheng et al, 2016), few studies have reported the viscosity of single particles consisting of inorganic species covering the RH range to high salt concentrations (Power et al, 2013;Rovelli et al, 2019). Herein, the RH-dependent viscosity was quantified for particles consisting of Mg(NO 3 ) 2 / H 2 O or Ca(NO 3 ) 2 / H 2 O determined at 293 ± 1 K upon dehydration using the bead-mobility and poke-and-flow techniques.…”
Section: Viscosities Of Particles Consisting Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the abundant mass of inorganic species in the atmosphere (Jimenez et al, 2009;Cheng et al, 2016), few studies have reported the viscosity of single particles consisting of inorganic species covering the RH range to high salt concentrations (Power et al, 2013;Rovelli et al, 2019). Herein, the RH-dependent viscosity was quantified for particles consisting of Mg(NO 3 ) 2 / H 2 O or Ca(NO 3 ) 2 / H 2 O determined at 293 ± 1 K upon dehydration using the bead-mobility and poke-and-flow techniques.…”
Section: Viscosities Of Particles Consisting Ofmentioning
confidence: 99%
“…Aerosol particles are emitted from various natural (e.g., the ocean and plants) and anthropogenic (e.g., transportation and fuel combustion) sources, as well as being produced by gas-to-particle conversion and equilibration processes due to chemical processing of gaseous species in the atmosphere (e.g., sulfur dioxide, nitrogen oxides, ammonia, and volatile organic compounds). Submicron-sized aerosol particles mainly consist of organic materials and inorganic salts (Jimenez et al, 2009;Huang et al, 2015;Cheng et al, 2016). Depending on the location and the season, the organic mass fraction of submicron particles ranges from ∼ 20 % up to ∼ 90 % (Zhang et al, 2007;Jimenez et al, 2009;Hao et al, 2014;Huang et al, 2015;Cheng et al, 2016;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These VOCs can be oxidized in the atmosphere, and the oxidized products can form secondary organic aerosol (SOA) (Hallquist et al, 2009;Ervens et al, 2011). SOA accounts for 20 %-80 % of the mass of atmospheric aerosol particles (Zhang et al, 2007;Jimenez et al, 2009) and plays an important role in climate, air quality, and public health (Kanakidou et al, 2005;Jang et al, 2006;Solomon, 2007;Baltensperger et al, 2008;Murray et al, 2010;Wang et al, 2012;Pöschl and Shiraiwa, 2015;Shiraiwa et al, 2017;Shrivastava et al, 2017a, b). Despite the importance of SOA, many of the physicochemical properties of SOA remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion rates within SOA can also affect multi-phase reactions (Shiraiwa et al, 2011;Zhou et al, 2013;Steimer et al, 2014;Houle et al, 2015;Li et al, 2018), the extent of long-range transport of pollutants (Zelenyuk et al, 2012;Zhou et al, 2013;Mu et al, 2018), ice nucleation (Murray et al, 2010;Wang et al, 2012;Wilson et al, 2012;Ladino et al, 2014;Schill et al, 2014;Knopf et al, 2018), and crystalline of salts (Murray, 2008;Murray and Bertram, 2008;Bodsworth et al, 2010;Song et al, 2013;Ji et al, 2017;.…”
mentioning
confidence: 99%